Increasing the Role of Workers Through the Sayang Warga Applications in Efforts to Prevent Endemic Dengue Fever in Surabaya City - Yudhastuti, Ririh; Lusno, Muhammad Farid Dimjati; Notobroto, Hari Basuki; Arfiani, Novi Dian; Sulistyorini, Lilis; Azizah, R.; Mukono, J.; Keman, Soedjajadi; Sudarmaji, Sudarmaji; Adriyani, Retno; Prasasti, Corie Indria; Lestari, Kusuma Scorpia; Diyanah, Khuliyah Candraning; Pawitra, Aditya Sukma; Husnina, Zida (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2024)
Abstract. Dengue fever (DHF) is a significant public health problem in Surabaya City, posing challenges in prevention efforts. This study aims to explore the potential of the Sayang Warga application in increasing the role of community cadres in DHF prevention efforts. The purpose of this Community Service is to educate about Dengue Fever Prevention and the Sayang Warga application Kader Surabaya Hebat mothers to increase the knowledge of Kader Surabaya Hebat mothers to prevent Dengue Fever.. The results of this study The results of the questionnaire showed 70.2% of participants said that the theme taken was very good, 26.67% stated that it was good and 2.98% stated that it was sufficient. This shows that the theme taken is exciting and liked by the participants. Evaluation is also carried out on the participants of the service activities by doing the preetest and postest carried out on the theme taken. The pretest results showed an average score of 75 and the posttest results with an average score of 100. Community service at the Sawahan Health Center, Sawahan Subdistrict, Surabaya City is very beneficial for Surabaya Hebat Cadres because it can increase their knowledge about dengue hemorrhagic fever and the Dear Citizen Application.